Twitter, Rant Account and Loneliness: The Role of Self-Criticism in Loneliness - Maridin, Zizi Zahra Zalyanti; Salvi, Vania Zahra Anisa; Musa, Moh Harun Ar Rosyid; Rahmawati, Yuliana Mukti (Universitas Negeri Malang, 2025)
Amid the increasingly diverse challenges of life, social media often becomes an outlet for releasing overwhelming stress. Some individuals choose platform X (formerly Twitter) due to its text-based format, which makes it easier for users to share emotional expressions in written form. This study aims to analyse the contribution of self-criticism in loneliness. The population in this study consists of active rant account users aged 18–25, selected using purposive sampling. A total of 96 participants were involved. The instruments used in this study include adaptation of the UCLA Loneliness Scale and the Forms of Self-Criticising/Attacking & Self-Reassuring Scale (FSCRS), both of which were adapted into Indonesian. The UCLA scale uses a 4-point Likert scale to measure the level of loneliness, while the FSCRS uses a 5-point Likert scale to assess levels of self-criticism. Both of the measuments using Cronbach alfa for their reliability and content validity. The result finds there is significant influence of self-criticism in loneliness. This finding is relevant particularly in understanding factors that affect individuals' mental well-being. Future research is recommended to conduct longitudinal studies to understand how the influence of self-criticism and loneliness evolves over time, and to explore the possibility of other variables influencing this relationship.